Volar plating of isolated ulna shaft fractures - K., Avinash C.; D., Keshava Murthy; V., Goutham D.; G., Sachin H. (International Journal of Research in Orthopaedics, 2023)
Background: Dorsal plating for ulna shaft fracture is a common practice. But this is associated with hardware prominence on the dorsal subcutaneous border of ulna necessitating implant removal on later days. Volar surface of ulna is flat similar to radius volar surface with good muscle cover reducing the problem of hardware prominence. So, we wanted to study the outcome of volar plating of ulnar shaft fractures. Methods: Ten patients satisfying our inclusion criteria underwent volar plating using volar approach between FCU and ECU and 3.5 DCP was placed on flat volar surface of ulnar shaft under thick muscle cover of FCU and FDP. Results: Out of 10 patients, 7 were acute fractures, 2 were neglected non unions and 1was non-union with implant insitu. Bone graft was used in non-union cases. All fractures united at 6-9 month post op without any complications. Conclusions: Isolated ulnar shaft fractures are common orthopaedic injuries. Displaced fractures require stabilization with dynamic compression plate (DCP). Application of implant on its volar aspect in distal 2/3rd fractures is easy due to flat surface and avoids complications related to hard ware prominence and subsequent need for implant removal.